2014
DOI: 10.1353/hpu.2014.0086
|View full text |Cite
|
Sign up to set email alerts
|

Community Health Center Provider and Staff’s Spanish Language Ability and Cultural Awareness

Abstract: Many community health center providers and staff care for Latinos with diabetes, but their Spanish language ability and awareness of Latino culture are unknown. We surveyed 512 Midwestern health center providers and staff who managed Latino patients with diabetes. Few respondents had high Spanish language (13%) or cultural awareness scores (22%). Of respondents who self-reported 76–100% of their patients were Latino, 48% had moderate/low Spanish language and 49% had moderate/low cultural competency scores. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Lack of Spanish-speaking providers or providers that understand Hispanic culture has led to suboptimal communication and strained patient-provider relationships (Perez Jolles et al, 2019). Insufficient provider understanding of non-Western models of care has also resulted in Hispanic individuals avoiding discussion of traditional beliefs and practices for fear of judgment and ridicule (Baig et al, 2014;Perez Jolles et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Lack of Spanish-speaking providers or providers that understand Hispanic culture has led to suboptimal communication and strained patient-provider relationships (Perez Jolles et al, 2019). Insufficient provider understanding of non-Western models of care has also resulted in Hispanic individuals avoiding discussion of traditional beliefs and practices for fear of judgment and ridicule (Baig et al, 2014;Perez Jolles et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Adequately trained interpreters are necessary and are a great addition to the health care team ( 99 102 ). Sometimes, patients' family members are asked to serve as interpreters.…”
Section: The a To Z List For Managing Type 2 Diabetes In Culturally Dmentioning
confidence: 99%
“…Another study observed healthcare providers' Spanish-language abilities related to diabetes education and management (Baig et al, 2014). The researchers surveyed more than 600…”
Section: Bilingual and Multicultural Academic Trainingmentioning
confidence: 99%
“…While the benefits of cultural competency training are equally important, linguistic training is sometimes not included with cultural competency training (ASHA, 2014c). Furthermore, to assume that linguistic competence and cultural competence go hand in hand is often a mistake as the content provided in each type of training is distinct (Baig et al, 2014). Though these concepts are often presented as a total package, separating language proficiency from the cultural component for training purposes may prove to be beneficial.…”
Section: Bilingual and Multicultural Academic Trainingmentioning
confidence: 99%